2020
DOI: 10.21037/jtd-19-3345b
|View full text |Cite
|
Sign up to set email alerts
|

General patient satisfaction after elective and acute thoracic surgery is associated with postoperative complications

Abstract: Background: Patient's satisfaction has been regarded as a subjective reflection of the quality of care received by patients during their hospital stay. However, which factors may influence patient satisfaction in different healthcare settings needs to be determined. Methods: Cross-sectional investigation of satisfaction at the time of discharge in 52 consecutive patients admitted in a UK Referral Centre for Thoracic Surgery for either elective (41 patients) or acute (11 patients) procedures. We evaluated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…Patient satisfaction with pain management and overall hospital experience play a role in postoperative pain . In our study, the patient’s global satisfaction with pain control at 30 days was similar to that of previous studies . However, the numerical rating of neuropathic pain and the rate of patients requiring analgesia consumption at 30 days was surprisingly high.…”
Section: Discussionsupporting
confidence: 87%
“…Patient satisfaction with pain management and overall hospital experience play a role in postoperative pain . In our study, the patient’s global satisfaction with pain control at 30 days was similar to that of previous studies . However, the numerical rating of neuropathic pain and the rate of patients requiring analgesia consumption at 30 days was surprisingly high.…”
Section: Discussionsupporting
confidence: 87%
“…When patients experience complications after surgery their self-reported perception of the care they received is negatively impacted. Patients are less likely to recommend the hospital and are more likely to perceive the hospital staff as unresponsive ( 43 - 45 ). Although not directly investigated in the study by Gurland et al , one may theorize that if a patient is less likely to recommend the hospital, they may also be less likely to recommend the surgeon.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical complications can lead to significant psychosocial distress, depression, anxiety and can negatively affect a patient’s quality of life ( 45 ). For example, when given the choice for management of prostate cancer, patients feeling anxious or depressed are more likely to prefer radical treatment options rather than active surveillance, as active surveillance can be anxiety producing ( 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of no association between suffering from postoperative complications and satisfaction are not supported by the literature. Previous studies report lower patient satisfaction among surgical and medical patients who suffered from postoperative complications or medical adverse effects [ 4 , 14 , 21 ]. Patient satisfaction involves several aspects, including the quality of the treatment, clinical outcome, and more subtle aspects, such as the relationship between patients and healthcare personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Even if postoperative complications usually can be treated and healed, some studies have shown inferior patient satisfaction among patients who suffered complications [ 4 , 14 , 21 ]. We aimed to estimate the risk of postoperative complications after surgery for LSS using two different data sources to better estimate the frequency, and to demonstrate the differences between the two methods for recording postoperative complications.…”
Section: Introductionmentioning
confidence: 99%